An echo score raises the suspicion of cardiac amyloidosis in Chinese with heart failure with preserved ejection fraction - Hong Yang; Rui Li; Fei Ma; Ye Wei; Yujian Liu; Yang Sun; Xingwei He; Hesong Zeng; Jiangtao Yan; Dao Wen Wang; Hong Wang (ESC Heart Failure, 2022)
Abstract Aims Transthyretin cardiac amyloidosis (ATTR‐CA) has been realized as an important cause of heart failure with preserved ejection fraction (HFpEF). We aim to provide insights into its prevalence in Chinese HFpEF patients, which is not known to date, using increased wall thickness (IWT) score by echocardiography. Methods Consecutive patients with HFpEF (EF ≥ 40%) and IWT (≥12 mm) were prospectively screened. Echocardiography was performed, and the IWT score incorporated relative wall thickness, E/e′ ratio, longitudinal strains, and tricuspid annular plane systolic excursion, and septal apical‐to‐base ratio was calculated. ATTR‐CA was defined as score ≥8 in the absence of serum and urine free light chain. Results Six hundred twenty‐four HFpEF patients from January 2019 to December 2021 were enrolled, of which 65.2% were males and the median (interquartile range [IQR]) age was 66 (IQR 57, 73) years. Thirty‐three patients (5.3%, 95% CI 3.5–7.0%) were with score ≥8, and 33.3% were females. They were younger (58 vs. 69 years, P < 0.001), had higher NT‐proBNP (6525.0 vs. 1741.5 pg/mL, P < 0.001) and troponin I (105.2 vs. 27.7 pg/mL, P = 0.001) level, and lower LVEF (47% vs. 57%, P < 0.001) compared with the patients with score <5. In the internal cohort (82 patients) who had undergone scintigraphy, the IWT score ≥8 was shown to have a sensitivity of 85.7% (95% CI 56.2–97.5%) and a specificity of 92.6% (95% CI 83.0–97.3%) for diagnosing CA, and the IWT score <5 had great accuracy in excluding CA with the negative predictive value of 100%, supporting the clinical usefulness of the IWT score to guide further dedicated testing for ATTR‐CA. Conclusions The IWT score by echocardiography was an excellent tool for screening ATTR‐CA in HFpEF. In Chinese HFpEF patients associated with a hypertrophic phenotype, the proportion of highly suspected ATTR‐CA as detected by IWT score ≥8 was 5.3%, lower than the reported prevalence of ATTR‐CA in non‐Asian patients with the disease.